Art, ideology, & economics in Nazi Germany : the Reich chambers of music, theater, and the visual arts - Steinweis, Alan E. 1957- (Univ. of North Carolina Press, 1993)
From 1933 to 1945, the Reich Chamber of Culture exercised a profound influence over hundreds of thousands of German artists and entertainers. Subdivided into separate chambers for music, theater, the visual arts, literature, film, radio, and the press, this organization encompassed several hundred thousand professionals and influenced the activities of millions of amateur artists and musicians as well. Alan Steinweis focuses on the fields of music, theater, and the visual arts in this first major study of Nazi cultural administration, examining a complex pattern of interaction among leading Nazi figures, German cultural functionaries, ordinary artists, and consumers of culture. One of the most persistent generalizations to emerge from research on Nazi Germany is the notion of a German artistic and cultural establishment at the mercy of a totalitarian regime determined to mobilize the arts for its own ideological purposes